The present-day state of tectonic stress in the Darling Basin, Australia: Implications for exploration and production - Rajabi, M.; Tingay, Mark; Heidbach, O. (Elsevier, 2016)
Knowledge of the full present-day stress tensor and pore pressure has significant applications in the exploration and production of conventional and unconventional hydrocarbon reservoirs. The Darling Basin of New South Wales, Australia, is an old sedimentary basin (Late Cambrian/Silurian to Early Carboniferous) in which there was limited information about the present-day stress field prior to this study. In this paper we evaluate the contemporary stress field of the Darling Basin using a dataset from recent exploration wells and perform a geomechanical risk assessment with respect to borehole stability, fracture/fault generation and reactivation. Our interpretations of borehole failures in borehole image logs reveal a prevailing east-west orientation of the maximum horizontal stress throughout the Darling Basin. The estimates of the magnitudes for the vertical, minimum and maximum horizontal stress in the studied wells indicate a transition between thrust and strike-slip faulting stress regime at 600–700 m depths, where the magnitude of vertical stress and minimum horizontal stress are close to each other. However, the presence of borehole breakouts and drilling-induced tensile fractures, that we observe in the image logs at greater depths (900–2100 m) indicate a transition into a strike-slip tectonic stress regime below a depth range of approximately 700–900 m. These findings are in agreement with overcoring stress measurements east and west of the investigated wells. Furthermore, there are several Neogene-to-Recent geological structures in the study area that indicate thrust faulting with an east-west oriented maximum horizontal stress orientation around this old sedimentary basin. The consistency between the orientation of maximum horizontal stress determined from wellbore data and neotectonic structures is significant, and implies that horizontal stress orientations derived from very recent geological features may be valuable inputs to geomechanical models in the absence of wellbore or other data. However, the recent surface geological structures suggest a thrust faulting stress regime that is in slight contrast to the transition between thrust and strike-slip stress regime (SH > Sh ~ Sv) indicated by petroleum data, and highlights a potential pitfall of using neotectonic structures in geomechanical models. In particular, careful attention and verification should be made when using neotectonic structures for input, calibration or confirmation of geomechanical models, especially in intraplate tectonic settings such as Australia.